INTEGRATION OF LINEAR PROGRAMMING AND QUEUEING MODELS (M/M/s) IN THE OPERATIONAL OPTIMIZATION OF NONGKIBAR CAFE, BANDUNG - Ivonne Ayesha; Rhiza Villani; Hoerul Dwi Natya Fauzan; Mugni Nurul Ilmi; Annisa Desfia Nur Fadilah; Anastasya Salsabila Alika Putri; Neng Lisda Sa’adah; M. Fariel Syima (Journal of Social and Economics Research, 2025)
This study aims to optimize the operations of Kedai Kopi Nongkibar Bandung using an operations research approach, focusing on production and service during peak hours. The methods employed include Linear Programming (LP) to determine the optimal production combination of three main menu items (Kopi Lemon, Blue Hawaiian, and Nasi Goreng Yang Zhou) and M/M/s queuing model analysis to evaluate service system performance. Data were collected through direct observation, interviews, and operational documentation, including production time per menu, equipment capacity, workforce allocation, and customer arrival patterns. The LP results indicate an optimal production combination of X₁=75 cups of Kopi Lemon, X₂=45 cups of Blue Hawaiian, and X₃=100 portions of Nasi Goreng Yang Zhou, achieving a maximum daily profit of IDR 4,420,190. Sensitivity analysis reveals that the main constraint is the physical production capacity of each menu, rather than barista working hours. Increasing barista hours without expanding production capacity does not effectively enhance profit. Queuing model analysis shows that the optimal scenario is achieved with four baristas during peak hours, reducing customer waiting time to under two minutes. Implementing barista specialization according to menu complexity effectively minimizes bottlenecks, accelerates service, and improves operational efficiency. These findings provide a quantitative basis for cafe managers to design resource allocation and menu production priorities, highlighting the importance of integrating production capacity planning and workforce management to enhance operational performance and customer satisfaction.